Conceptual Metaphor In Song Lyrics Pierce The Veil’s Collide With The Sky Album - Putu Ersta Adi Lunga Atmaja; I Made Rajeg; Made Detriasmita Saientisna (Denpasar Institute, 2026)
This study addresses the role of metaphor in song lyrics, a key issue in understanding how abstract emotions and experiences are linguistically and cognitively represented, particularly within contemporary music. Employing a descriptive qualitative method, the research analyzes twelve selected songs from the Collide With The Sky album. The study is grounded in Lakoff and Johnson’s (2003) conceptual metaphor theory, which classifies metaphors into structural, orientational, and ontological types. Metaphorical expressions within the lyrics are systematically identified, categorized, and interpreted through their conceptual mappings between source and target domains. The analysis reveals a total of 113 metaphorical expressions, comprising 34 structural metaphors, 11 orientational metaphors, and 68 ontological metaphors. These findings demonstrate that metaphor plays a crucial role in shaping the emotional tone, thematic complexity, and stylistic expression of the lyrics. Furthermore, metaphor functions as a cognitive tool that helps clarify abstract emotions and ideas, enabling the articulation of personal experiences, internal conflicts, and emotional struggles in a poetic and meaningful manner.